Penerapan Integrated Reporting Dan Kaitannya Dengan Nilai Perusahaan Di Indonesia - Damayanti, Ameilia; Mira Munira; Herlan; Adinda Dwi Putri (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2024)
This research aims to determine the application of integrated reporting, profitability, and liquidity on company value. The data used in this research is secondary data obtained from financial reports on idx.co.id. The population in this study consists of infrastructure companies listed on the Indonesia Stock Exchange. Using purposive sampling technique, the sample consisted of 11 companies with an observation period of five years from 2019 to 2023. The research method used is multiple linear regression. The results of this research prove that the implementation of integrated reporting affects the company's value, as well as liquidity, but profitability does not affect the company's value.